Genetic evaluation of BC₂F₂ and BC₂F₃ populations derived from a cross between β-carotene-rich field corn (Zea mays L.) and sweet corn (Zea mays var. saccharata) for sweetness and agro-morphological traits - Manjunath, P.; Phurailatpam, Ranjit Sharma; Khoyumthem, Pramesh; Thokchom, Renuka Devi; Thokchom, Nepolian Singh; Mishra, Lokesh Kumar; Natesan, Senthil; Balamurugan, Mohanapriya; Ravichandran, Shivakumar (Journal of Phytology, 2025)
CAUM66 was found to be a superior landrace and its improved version CAUM66β+ inbred line having a high productivity and beta carotene content. This landrace was reported to have a wide popularity among local farmers of Manipur and hence is a promising parent for breeding programs. DBT16 is the biofortified sweetcorn (inbred line) was found to be a superior inbred parental line during hybrid yield trial having a high productivity and sugar content. So, this study evaluated the genetic variability, heritability, and trait distribution pattern of a BC2F2 and BC2F3 population derived from a cross between β-carotene-rich field corn (CAUM66β⁺) and biofortified (β-carotene-rich) sweet corn (DBT16). Fourteen agro-morphological traits were analysed for variability, The GCV and PCV were ranged from 3.99% to 13.49% and 5.51% to 14.75% and it revealed that the estimates of PCV was higher than GCV for all the traits studied in both the populations, revealing influence of environment. Heritability and GAM estimates ranged from 46.83% to 97.38% and 5.95% to 26.10%, respectively, revealed that the agro-morphological traits viz., cob length, number of tassel-branches, tassel length, cob girth and number of kernels-per row has contributed maximum towards variability depicting the involvement of additive genetic effects and good selection potential. Skewness and kurtosis analysis revealed that number of tassel branches exhibited positive skewness and leptokurtic distribution in BC2F2 population, while most traits showed negative skewness and platykurtic curves, indicating polygenic control. Similarity percentage of lines in BC2F3 population towards recurrent parent, ranged from 79.12% to 82.88% and TSS ranged 14% to 18%. Based on these parameters best four lines from each BC2F3 progeny i.e., CAUM66β+ × DBT16 – 7 – 25 – 5 – 15 – 14 and CAUM66β+ × DBT16 – 3 – 5 – 16 – 29 – 17 was selected and these lines can be utilized in future breeding programs aimed at biofortifying sweetcorn. In the present study, successful introgression of the sweetness allele into field corn led to the development of improved lines, which exhibit strong potential for utilization in hybrid breeding programs.